ACTIVITY BOOK BERBASIS CERITA BERGAMBAR UNTUK MENUNJANG KEMAMPUAN PEMAHAMAN CERITA PENDEK - Lintang Apriliana; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the lack of understanding in learning Indonesian, especially in the material of writing short stories and understanding of several elements in a short story text, therefore the need for the use of more creative and effective learning media for students. The case that occurred was that around 40% of students in the class did not master the understanding of reading texts including main ideas and supporting ideas. This will be an impact because students can only read without understanding the contents of the reading they read. This problem arises, so it is necessary to optimize more innovative and effective teaching materials for students. This researcher uses the Thiagarajan 4D development paradigm which includes four stages: definition, design, development, and distribution. The participants of this study were elementary school students in grade IV at an elementary school in Surabaya. The results of this study indicate that the Activity Book learning media based on illustrated narratives is considered satisfactory without the need for revision. Through competent media, linguistic, and material evaluators. The final results of all validators produced 95.5% for material experts, 85% for language experts, and 85.5% for media experts. With a fairly appropriate description.